Combinação de classificadores para detecção de fraudes em sinistros de automóveis. - Rodrigues, Luis Alexandre (2014)
This work presents a process to detect suspected cases of fraud at automobile claims dataset, which is evaluated the economic created by it. Because of a detection process presenting misclassific ation, it is necessary to evaluate the financial economy made by the process not only its accuracy in detecting suspected cases of fraud. This process uses a combination of classifiers, with C4.5 Decision Tree, Naive Bayes and Support Vector Machine, const ructed by samples of the data set with automobile claims. This way, the process defined by this work can obtain the balance between the accuracy of classification and the financial economy.